Acute exposure to the fungicide penconazole affects some biochemical parameters in the crayfish (Astacus leptodactylusEschscholtz, 1823) - Uckun, Aysel Alkan; Oz, Ozden Barim (Springer Heidelberg, 2020)
Penconazole is one of the most widely used fungicides all over the world, and since it spreads to large environments, its toxic effects on non-target organisms are of great concern. The toxic effects of penconazole on crayfish (Astacus leptodactylus), which is a bioindicator in freshwater ecosystems and consumed economically, are not known. Therefore, in this study, the purpose was to contribute to the literature on the potential harmful effects of penconazole on a non-target species,Astacus leptodactylus. For this aim, the acute toxicity (96 h) of penconazole was examined. The 96-h LC(50)value of penconazole was detected as 18.7 mg L-1. Four concentrations of penconazole (18.7 mg L-1, 9.35 mg L-1, 4.68 mg L-1, 2.34 mg L-1) were applied to crayfish for 96 h. The results showed that penconazole had destructive effects on esterase mechanisms by inhibiting acetylcholinesterase (AChE) and carboxylesterase (CaE) activities. Significant increases were observed in all antioxidant parameters (superoxide dismutase (SOD), glutathione peroxidase (GPx), glutathione reductase (GR), glutathione S-transferase (GST), reduced glutathione (GSH), malondialdehyde (MDA)) in all doses except the lowest concentration (2.34 mg L-1). All adenosine triphosphatase (ATPase) activities (Na+/K+-ATPase, Mg2+-ATPase, Ca2+-ATPase, total ATPase) had significant dose-related inhibition in both gill and muscle tissues. In summary, our findings show that acute penconazole administration to crayfish causes significant toxic effects on esterase, antioxidative parameters, and metabolic enzymes.
Keywords: Antioxidant; Biomarker; Crustacean; Oxidative stress; Pesticide; Toxicity